Vivência grupal: estratégia de engajamento no auto-cuidado em diabetes - Ataíde, Marcia Barroso Camilo de (2004)
Despite so many efforts to maximize the adhesion of diabetic patient to follow his treatment, he does not incorporate seif care altitudes, which are so much necessary for his quality of life. Before this fact, the thesis is held, that group work is a strategy which eases the engagement process of diabetic into self care. This research had, as a general objective, to analyze the engagement process into self care of diabetic persons who took parí in group educative experiences. It is an action-research, with a mostly qualitative approach, undertaken at the Integrated Medicai Assistance Nucleus, of the University of Fortaleza, at the district of the same name. The partakers were thirteen diabetic women, who, throughout the period from March to October 2003, participated of the three stages of the research: Identification of self care deficits, educative group activities for self care in diabetes and focal group. The OrenTs theory on self care déficit was of use to select subjects and programming group activities. Information were analyzed to the light of the Health Promotion Conferences, and of scholars of Education on Health and on Diabetes. The results pointed out that the deficits in self care which hindered the engagement of women were: limitation to make judgment, indicating unbalance in health maintenance, lack of knowledge about their health condition. Such deficits are related to biologic and psychosocial factors, which leads to consider that the relationship between those factors influences the engagement on self care of diabetic women. All the diabetic women (13) did engage in self care, being the case that 8 of them developed abilities to deal with all the self care deficits - total engagement - and the other (5) developed at least one of the abilities to deal with the self care deficits. The engagement in self care was Consolidated by women when they incorporated an altitude of self care, such as participation in walking group in the community of Dendê, the continuity of pharmacological treatment as from the reflective and contextual discussions towards the reality they experienced and from the adhesion to healthy nutrition. The ignorance and doubts about pathology were reduced to a minimum, as there was a knowledge build-up pervaded by mutual dialog and learning. In the process of engagement, it is necessary to consider that those women live away of fundamental health conditions, besides the fact that they do not accept the disease. Living with violence, social inequality, unemployment, precariousness of health Services, lack of financial conditions to buy adequate foods and being assisted in the hegemonic model that prioritizes biologic features, the group experiences of education on self care gave chance to the engagement on self care of those women...There was, within the group, a dialog related cooperative construction, enabling the engagement on self care through the understandjng of the biologic and psychosocial factors that guide the process of engagement.